Ndondondwane: the significance of features and finds from a ninth-century site on the lower Thukela River, Natal - Loubser, J.H.N. (Southern African Humanities, 2021)
An earlier excavation of Ndondondwane was followed-up in order to find more traces of structures and ceramic sculpture. Three clusters of cultural material remains were excavated: the mound area, the dung area, and the dage (baked clay) area. The mound area resulted from at least five dumping episodes: the first is associated with hut floor(s), the second with the demolition of the hut(s), the third with the dumping of grey ash, the fourth with the building of an enclosure, and the final episode with the construction and demolition of an iron furnace. Sculputred clay objects were most likely associated with the enclosure in the mound area. Similar pieces also came from the dung area, which comprised at least two layers: an early layer of hard dung and a later layer of soft dung and ash. The daga area also comprised more than one layer: excavations yielded pockets of ash underneath intact fragments of floor. As the mound and dung areas are fairly centrally located when compared with the rest of the surface scatters at the site, it is argued that sculptured ceramic pieces and associated structures are most likely the result of initiation activities.